The tyranny of research? Urban regeneration, ethnography, and the problem of unintended consequences. Issue 4 (8th August 2017) - Engelsman, Udi; Rowe, Mike; Southern, Alan
Abstract: Following a case study of community development in public housing in Liverpool, UK, we present in this article three potential tyrannies of research. We show the tyranny of the researcher, of the method selection, and of the data. In so doing, we identify the methodological challenges of conducting research that seeks to privilege the voices and perspectives of the subjects in a participatory project. We examine whether the dangers of tyranny are present in ethnographic and other participatory forms of research as much as in the practice of participatory development. We argue that, by acknowledging the potential tyranny of research, we are able to highlight the importance of a critical and reflexive research practice, particularly for ethnographers working in a participatory context.